2021
DOI: 10.1021/acs.macromol.1c00343
|View full text |Cite
|
Sign up to set email alerts
|

Confined Polymers in a Poor Solvent: The Role of Bonding to the Surface

Abstract: We analytically predict the concentration profile of a long polymer chain in a poor solvent, confined between two walls where some of its monomers can form strong bonds with the walls. In contrast to adsorption boundary conditions, these concentration profiles can vary nonmonotonically. Boundary conditions that lead to a decrease in the monomer concentration at the walls (at fixed, total monomer concentration) show a transition between concentration profiles in which the polymer concentration is organized peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For example, self-attraction can lead to chromatin collapse (as in refs. 23 and 24 ). Since we are interested in identifying the dominant forces, we estimate an upper bound on the possible values of R g and subsequently on the pressures p p .…”
Section: Forces Involved In Nuclear Volume Determinationmentioning
confidence: 99%
“…For example, self-attraction can lead to chromatin collapse (as in refs. 23 and 24 ). Since we are interested in identifying the dominant forces, we estimate an upper bound on the possible values of R g and subsequently on the pressures p p .…”
Section: Forces Involved In Nuclear Volume Determinationmentioning
confidence: 99%
“…For simplicity we consider the case where both types of monomers have the same molecular size . Motivated by recent experimental and theoretical studies on chromatin organization showing that chromatin behaves as a self-attractive polymer (polymer in poor solvent) ( Amiad-Pavlov et al, 2021 ; Bajpai et al, 2021 ; Adame-Arana and Safran, 2021 ), we model both blocks (in the absence of chromatin-binding protein complexes) as being in poor solvent conditions; both blocks phase separate from the aqueous phase, consistent with the experiments. However, due to the difference in attraction of AA vs. BB, the two types of blocks will undergo a further, microphase separation, reminiscent of the data in Amiad-Pavlov et al, 2021 , where acetylated chromatin is mostly found surrounding regions of higher density of chromatin.…”
Section: Resultsmentioning
confidence: 65%
“…For simplicity we consider the case where both types of monomers have the same molecular size a. Motivated by recent experimental and theoretical studies on chromatin organization showing that chromatin behaves as a self-attractive polymer (polymer in poor solvent) [19,22,51], we model both blocks (in the absence of chromatin-binding protein complexes) as being in poor solvent conditions; both blocks phase separate from the aqueous phase, consistent with the experiments. However, due to the difference in attraction of AA vs. BB, the two types of blocks will undergo a further, microphase separation, reminiscent of the data in [19], where acetylated chromatin is mostly found surrounding regions of higher density of chromatin.…”
Section: B Theoretical Model: Chromatin As a Multiblock Copolymermentioning
confidence: 89%